2017
DOI: 10.1021/acs.inorgchem.7b01060
|View full text |Cite
|
Sign up to set email alerts
|

Dysprosium Heteroleptic Corrole-Phthalocyanine Triple-Decker Complexes: Synthesis, Crystal Structure, and Electrochemical and Magnetic Properties

Abstract: Two triple-decker dinuclear sandwich dysprosium complexes, which are represented as Dy[Pc(OCH)][Cor(FPh)] (1) and Dy[Pc(OCH)][Cor(ClPh)] (2), were synthesized and characterized by spectroscopic and electrochemical methods in nonaqueous media. Their electronic structures were also investigated on the basis of TD-DFT calculations. The sandwich triple-decker nature with the molecular conformation of [Pc(OCH)]Dy[Cor(FPh)]Dy[Pc(OCH)] for compound 1 was unambiguously revealed by single-crystal X-ray diffraction anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Section 3.1), as evidenced from AC magnetic susceptibility measurements performed for dysprosium(III) complexes Dy 2 [(PentO) 8 Pc] 2 [(p-XPh) 3 Cor], X = F or Cl. 164 The presence of three protons in corroles suggests that the closed-shell form of triple-decker complexes should be anionic in nature, which makes them different from trisphthalocyaninates, where the charge of two trivalent REE ions is balanced by the charge of three dianionic ligands. Thus, to stabilize the negative charge of the (M 3+ ) 2 (Cor 3À )(Pc 2À ) 2 species a counterion is needed.…”
Section: Sandwiches With Less-common Tetrapyrrolic Ligandsmentioning
confidence: 99%
“…Section 3.1), as evidenced from AC magnetic susceptibility measurements performed for dysprosium(III) complexes Dy 2 [(PentO) 8 Pc] 2 [(p-XPh) 3 Cor], X = F or Cl. 164 The presence of three protons in corroles suggests that the closed-shell form of triple-decker complexes should be anionic in nature, which makes them different from trisphthalocyaninates, where the charge of two trivalent REE ions is balanced by the charge of three dianionic ligands. Thus, to stabilize the negative charge of the (M 3+ ) 2 (Cor 3À )(Pc 2À ) 2 species a counterion is needed.…”
Section: Sandwiches With Less-common Tetrapyrrolic Ligandsmentioning
confidence: 99%
“…For photoluminescence, rare‐earth ions are usually used as luminescent centers for their high luminescence efficiency and adjustable emission color . Rare earth ions have magnetic anisotropy in magnetism, which makes them often used to make molecular‐based magnetic materials, such as single‐molecule magnets (SMMs) and single‐chain magnets (SCMs) . Not only that, rare‐earth ions are also used in other fields, such as bioassays, biological labels, light‐converting optical materials luminescent probes and light emitting diodes .…”
Section: Introductionmentioning
confidence: 99%
“…The Tb1 center is eight‐coordinated, involved in a distorted square antiprism geometry and bound completely to six oxygen atoms (O1, O3, O5, O7, O9 and O10) respectively, which from one bidentate chelating and four bridging bidentate 3,4‐DMBA − ligands. The Tb2 is also eight‐coordinated with six oxygen atoms (O2, O4, O6, O8, O11 and O13) from one coordination water, one monodentate 3,4‐DMBA − ligand and four bridging bidentate 3,4‐DMBA − ligands, resulting in a distorted triangular dodecahedral geometry (Figure ). From the Table , we can see the average bond length of Tb‐O is 2.348 Å, which is shorter than that of Tb‐N bond (2.571 Å) owing to the stronger coordination ability of the oxygen atoms, which have been confirmed that the 5,5′‐DM‐2,2′‐bipy ligands are lost firstly in the thermal decomposition process.…”
Section: Resultsmentioning
confidence: 99%